THE EFFECT OF BRAND TRUST AND BRAND EXPERIENCE ON BRAND LOYALTY THROUGH EMOTIONAL BRAND ATTACHMENT TO WARDAH COSMETICS - Arti Mayangsari; Harti Harti (Jurnal Mantik, 2022)
This study aims to determine the effect of brand trust and brand experience on brand loyalty to Wardah cosmetics customers, which is mediated through emotional brand attachment. All female consumers of Wardah Cosmetics are the population in this study. By using the purposive sampling method, 100 (one hundred) respondents were selected. The sample of this research must consist of female consumers who have used Wardah Cosmetics for a minimum of 17 years and have usedWardah Cosmetics products at least 2 (two) times. The strategy applied to collect data is to use a questionnaire with a Google form. To evaluate the data, this study applies the "Structural Equation Modeling (SEM)" technique based on variance, especially "Partial Least Square (PLS)", which is calculated with the SmartPLS 3.0 application. The equation models tested include the outer model, inner model, and hypothesis testing. The results showed that "brand trust affects brand loyalty, brand experience has not affected brand loyalty; emotional brand attachment affects brand loyalty, brand trust has not affected emotional brand attachment; brand experience affects emotional brand attachment; brand trust has not affected brand loyalty through emotional brand attachment; brand experience affects brand loyalty through emotional brand attachment.